Use of bioethanol byproduct for supplementary cementitious material production - Ataie, Feraidon F.; Riding, Kyle A. (My University, 2014)
Corn stover has the potential for use as a supplementary cementitious material (SCM) for concrete. The impact of distilled water and dilute acid pretreatments and post-treatments on the pozzolanic reactivity of corn stover ash (CSA) was studied. Additionally, the potential use of a bioethanol byproduct called high lignin residue (HLR) for SCM production was examined. Pretreated CSA and high lignin residue ash (HLRA) increased the early reactivity of cement paste when used as 20% replacement of cement in the system whereas unpretreated CSA was found to severely suppress the hydration reaction. The highest compressive strength was obtained from samples containing HLRA.
Keywords: Pozzolanic materials; Sustainable concrete; Bioethanol byproduct; High lignin residue ash